Spatial Analysis of Multichannel Surface EMG in Hemiplegic Stroke - Rasool, Ghulam; Afsharipour, Babak; Suresh, Nina L.; Rymer, William Z. (IEEE transactions on neural systems and rehabilitation engineering, 2017)
We investigated spatial activation patterns of upper extremity muscles during isometric force generation in both intact persons and in hemispheric stroke survivors. We used a 128-channel surface electromyogram (EMG) grid to record the electrical activity of biceps brachii muscles during these contractions. EMG data were processed to develop 2-D root mean square (RMS) maps of muscle activity. Our objective was to determine whether motor impairments following stroke were associated with changes in the muscle activity maps and in the spatial distribution of muscular activation. We found that, for a given subject, spatial patterns in muscle activity maps were consistent across all measured contraction levels differing only the RMS EMG. However, the maps from opposite arms (stroke-affected versus non-affected) of stroke survivors were significantly different from each other, especially when compared with the differences observed intact participants. Our analyses revealed that chronic stroke altered the size and location of the active region in these maps. The former is potentially related to disruption of fiber and tissue structure, possibly linked to factors such as extracellular fat accumulation, connective tissue infiltration, muscle fiber atrophy, fiber shortening, and fiber loss. Changes in spatial patterns in muscle activity maps may also be linked to a shift in the location of the innervation zone or the endplate region of muscles. Furthermore, the textural analysis of EMG activity maps showed a larger pixel-to-pixel variability in stroke-affected muscles. Alterations in the muscle activity maps were also related to functional impairment (estimated using Fugl-Meyer score) and to the degree of spasticity (estimated using the modified Ashworth scale). Overall, our investigation revealed that the muscle architecture and morphology were significantly altered in the chronic stroke.